An investigation of blended polymeric membranes and their gas separation performance - Farnam, M. (Royal Society of Chemistry, 2016)
This research work was carried out to investigate the influence of blending polymer membranes on the performance of CO2/CH4 separation. This was obtained via blending glassy and rubbery polymers at different concentrations, using solution casting and a solvent evaporation method. All fabricated membranes were characterized by field emission scanning electron microscopy (FESEM), thermo gravimetric analysis (TGA) and Differential Scanning Calorimetry (DSC). The membranes were observed to have a dense structure as depicted by FESEM, low residue solvent by TGA and a miscible homogeneous blend structure by DSC. The performance of CO2/CH4 separation of the new blend membranes was compared against that of pure PES membrane at pressures varying from 2 to 10 bar. The experimental results showed that the incorporation of rubbery polymer, polyvinyl acetate (PVAc), into pure polyethersulfone (PES), which is a glassy polymer, resulted in membranes having more efficient CO2 separation. However, by increasing the pressure, the permeability dropped because of the glassy behavior of the membranes. The significant improvement of CO2/CH4 selectivity by adding PVAc in comparison to pure PES membrane indicates that the rubbery polymer (PVAc) can be used to enhance CO2 separation from CO2/CH4 mixtures. Â© The Royal Society of Chemistry 2016.